Multi-culm bamboo composites as sustainable materials for green constructions: section properties and column behavior - Effendi Tri Bahtiar; Asep Denih; Gustian Rama Putra (Results in Engineering, 2023)
Round bamboo culms offer excellent sustainable materials for a green building construction. Round bamboo culms are tied or fastened into a multi-culm composite member to resist the heavier load. Circles externally touching each other can well model a multi-culm bamboo composite's section. This study aimed to obtain formulas for drawing a cross-section of a multi-culm bamboo composite, calculating its section properties, and then embedding them into a graphing calculator and spreadsheet. As many as nine full-sized single and multi-culm bamboo composite columns were tested in the laboratory to resist the buckling load until the failure occurred. The column acting as the sum of some individual culms capacity was considered. In addition, the embedded equations analyzed the multi-culm column working in unity as a composite. This study found that the multi-culm columns tend to inhibit the combination (pseudo-composite) behavior rather than acting as a perfect composite column or the sum of individual culm's capacities. A perfect composite columns approach resulted overestimated value of the multi-culm column's critical buckling load; on the other hand, the sum of individual culm's capacity approach approximated underestimated value. The weighted average approach with a weight coefficient of k = 1 explains the empirical critical buckling load-bearing capacity's variance very well.